2023
DOI: 10.1097/md.0000000000034094
|View full text |Cite
|
Sign up to set email alerts
|

Physical workplace violence in the health sector in Saudi Arabia

Aseel Khaled Alhassan,
Reem Tarik Alsaqat,
Fahad Saleh Al Sweleh

Abstract: Physical workplace violence (WPV) occurs worldwide, causing psychological and physical injuries. However, reports from Saudi Arabia investigating which specialty is the most exposed are scarce. This study aimed to determine the prevalence and circumstances related to physical WPV among all healthcare providers in Saudi Arabia in 12 months, as well as the consequences for both attackers and targets of physical WPV. This cross-sectional study included all healthcare providers registered with the Saudi Commission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This study is part of a research project focused on evaluating WPV in the health sector in Saudi Arabia. [ 19 ] It included all healthcare providers who were registered with the Saudi Commission for Health Specialties (SCFHS) and had been working for more than 1 year in the health sector (governmental or private) in Saudi Arabia by May 2019. The exclusion criteria were students, interns, employees of the administrative department, and providers who were not registered with SCFHS or had <1 year of work experience.…”
Section: Methodsmentioning
confidence: 99%
“…This study is part of a research project focused on evaluating WPV in the health sector in Saudi Arabia. [ 19 ] It included all healthcare providers who were registered with the Saudi Commission for Health Specialties (SCFHS) and had been working for more than 1 year in the health sector (governmental or private) in Saudi Arabia by May 2019. The exclusion criteria were students, interns, employees of the administrative department, and providers who were not registered with SCFHS or had <1 year of work experience.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported on an association between the years of experience and the occurrence of different forms of WPV, and most studies found this relationship to be inversely proportional [ 12 , 35 , 49 , 76 , 98 , 99 , 111 , 123 , 124 , 146 , 152 , 171 , 194 , 203 , 204 , 212 , 214 , 219 , 223 , 227 229 ]. We analyzed the forms of violence which had a higher prevalence for either men or women to examine any connection to years of work experience.…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed the forms of violence which had a higher prevalence for either men or women to examine any connection to years of work experience. Studies reported that men experiencing more verbal abuse [ 219 ], physical violence [ 123 , 146 , 171 ], and bullying [ 218 ] had the least work experience. Similarly, less experience as a factor for verbal abuse [ 98 ], sexual harassment [ 12 , 149 , 152 ], physical violence [ 124 ], horizontal violence [ 229 ], bullying [ 35 ] and aggression [ 159 ], in studies which reported women as victims of WPV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations